Predictors of Weight Change in Male HIV-Positive Injection Drug Users Initiating Antiretroviral Therapy in Hanoi, Vietnam. (6th July 2011) - Tang, Alice M.; Sheehan, Heidi B.; Jordan, Michael R.; Duong, Dang Van; Terrin, Norma; Dong, Kimberly; Lien, Trinh Thi Minh; Trung, Nguyen Vu; Wanke, Christine A.; Hien, Nguyen Duc
Abstract : We examined clinical and nutritional predictors of weight change over two consecutive 6-month intervals among 99 HIV-positive male injection drug users initiating antiretroviral therapy (ART) in Hanoi, Vietnam. The average weight gain was 3.1 ± 4.8 kg in the first six months after ART and 0.8 ± 3.0 kg in the following six months. Predictors of weight change differed by interval. In the first interval, CD4 < 200 cells/ μ L, excellent/very good adherence to ART, bothersome nausea, and liquid supplement use were all associated with positive weight changes. Moderate to heavy alcohol use and tobacco smoking were associated with negative weight changes. In the second interval, having a CD4 count <200 cells/ μ L at the beginning of the interval and tobacco smoking were the only significant predictors and both were associated with negative weight changes. We identified several potential areas for interventions to promote weight gain immediately after starting ART in this population. Studies are needed to determine whether improving weight prior to, or at, ART initiation will result in improved outcomes on ART.